2020
DOI: 10.21608/jbaar.2020.119755
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cardioprotective effect of l-carnitine and silymarin in cancer patients receiving anthracycline-containing chemotherapy

Abstract: BioBacta

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…All trials concluded that levocarnitine has a cardioprotective effect. Four trials studied levocarnitine as a single agent 4043 and one studied levocarnitine in combination with coenzyme Q (Table 1). 44 One systematic review was obtained 45 – this review did not draw any conclusions cited as due to insufficient data (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All trials concluded that levocarnitine has a cardioprotective effect. Four trials studied levocarnitine as a single agent 4043 and one studied levocarnitine in combination with coenzyme Q (Table 1). 44 One systematic review was obtained 45 – this review did not draw any conclusions cited as due to insufficient data (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…With the global trend in nutraceuticals and drug repurposing, a re-evaluation of the trials of these agents maybe worthwhile to reduce the cost of the burden of the cancer disease. 36,37,41…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation